{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Stitz-Zeager_College_Algebra_e-book

# 3 example 1193 let l1 be the line y m1 x b1 and let l2

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: , we get cos(2θ) = A−C , or (A − C ) sin(2θ) = B cos(2θ). We use this substitution B B sin(2 twice along with the Pythagorean Identity cos2 (2θ) = 1 − sin2 (2θ) to get 4A C = (A + C )2 − (A − C )2 cos2 (2θ) − 2B (A − C ) cos(2θ) sin(2θ) − B 2 sin2 (2θ) = (A + C )2 − (A − C )2 1 − sin2 (2θ) − 2B cos(2θ)B cos(2θ) − B 2 sin2 (2θ) = (A + C )2 − (A − C )2 + (A − C )2 sin2 (2θ) − 2B 2 cos2 (2θ) − B 2 sin2 (2θ) = (A + C )2 − (A − C )2 + [(A − C ) sin(2θ)]2 − 2B 2 cos2 (2θ) − B 2 sin2 (2θ) = (A + C )2 − (A − C )2 + [B cos(2θ)]2 − 2B 2 cos2 (2θ) − B 2 sin2 (2θ) = (A + C )2 − (A − C )2 + B 2 cos2 (2θ) − 2B 2 cos2 (2θ) − B 2 sin2 (2θ) = (A + C )2 − (A − C )2 − B 2 cos2 (2θ) − B 2 sin2 (2θ) = (A + C )2 − (A − C )2 − B 2 cos2 (2θ) + sin2 (2θ) = (A + C )2 − (A − C )2 − B 2 = A2 + 2AC + C 2 − A2 − 2AC + C 2 − B 2 = 4AC − B 2 Hence, B 2 − 4AC = −4A C , so the quantity B 2 − 4AC h...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online